Inclusive education: legislation and investments in continuous teacher training - Nunes , Maria Julia; Nascimento, Jussara Cassiano (Seven Editora, 2023)
This article is a bibliographic study that aims to present some discussions on the subject with emphasis on the investments that are happening in the continuing education of teachers to work in Inclusive Education. We present some regulations that are providing legal support for this training to take place. We emphasize that after the pandemic period and the return of students to face-to-face teaching, there has been a significant advance in the number of students who are in need of this specialized educational support and in this context we highlight the importance of bringing to the debate the ways in which the continuing education of teachers has been structured to work with this target audience. We dialogued with Silva (1986), Nóvoa (1995), Sassaki (1997), Carvalho (1998), Silva (2003), Silva (2006), Moreira (2009), according to Messiou and Ainscow (2015), and some regulations from the Ministry of Education that will be inserted in the construction of our arguments. Our perception is that this continuing education to deal with diversity needs to be built through investments in theoretical studies, in pedagogical practices developed on a daily basis with students and in discussions with peers, thus seeking pedagogical possibilities that will contribute to the socialization and mainly to enable access to knowledge for all students. DOI: https://doi.org/10.56238/devopinterscie-024